PEMETAAN CAPAIAN TUJUAN PEMBANGUNAN BERKELANJUTAN (TPB) DALAM BUDIDAYA PERIKANAN DENGAN MODEL SILVOFISHERY (STUDI KASUS: PERENCANAAN BUDIDAYA KEPITING SILVOFISHERY DI DESA PULAU CAWAN) - Gerhana Adjie (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2019)
Silfovishery is a fishery farming model that maintains the natural habitat of mangrove forests as a living medium for biota. The Indragiri Hilir Regency Government through the Fisheries Service in the 2018 budget year conducted a feasibility study of crab farming using the silvofishery method. In addition, Indragiri Hilir Regency is also very enthusiastic in carrying out the achievement of the Sustainable Development Goals (SDGs) in accordance with the mandate of Presidential Regulation Number 59 of 2017 concerning Implementation of the Achievement of Sustainable Development Goals. this study is a desk review of planning cultivation activities with silvofishry and the achievement of the Sustainable Development Goals. The implementation of aquaculture with silvofishery models can support the achievement of SDGs in the Environmental Pillar (5 indicators), Social (2 indicators) and Economy (1 indicator).